Gender in agricultural mechanization: Key guiding questions - Kawarazuka, Nozomi; Prain, Gordon; Forsythe, L.; Mayanja, S.; Mudege, Netsayi N.; Babini, C.; Polar, Vivian (International Potato Center, 2018)
This tool describes case studies of gender implications in mechanization in RTB crops, illustrating both positive and negative outcomes. GENNOVATE research has shown that the beneficiaries of mechanization tend to be the wealthier rather than the poorer farmers and more often men than women. However, results also reveal that women have strong interest in mechanization as a way to improve their own circumstances.